Analisis Dampak Perkebunan Kelapa Sawit Terhadap Sosial dan Ekonomi Masyarakat di Kabupaten Asahan - Muhammad Fadly Abdina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
North Sumatra has an area of around 14% of the total area of oil palm plantations in Indonesia or second only to Riau and the total area in 2009 could produce CPO of 3.18 million tons or around 17% of the total national CPO production. Increased production of oil palm plants found in Asahan district, should be directly proportional to the synergy of the development of oil palm plantations based on sustainability. Sustainable oil palm plantation development (Sustainable) is development that has a positive impact on the social, economic and cultural aspects of the communities around plantations, regionally and nationally. A comparative analysis of the impact of the development of oil palm plantations before and after can be done using t-test analysis of the contribution of farming before and after the development of oil palm plantations. The results of the t-test analysis of the contribution of farming before and after the development of oil palm plantations are: Before the development of oil palm plantations% other farm income from total farm household income (rubber, rice, livestock) by 38%, After the development of oil palm plantations% income oil palm farming to total farm household income of 62%. In this study, 62% of the total income of the farming family is obtained, so it is said that the contribution of large oil palm plantations is in accordance with the contribution criteria of 50-75% (large).